Qualitative and quantitative analysis of chemical constituents of Ptychopetalum olacoides Benth. Issue 3 (1st February 2018) - Tian, Xiao; Guo, Sen; He, Kan; Roller, Marc; Yang, Meiqi; Liu, Qingchao; Zhang, Li; Ho, Chi-Tang; Bai, Naisheng
Abstract: Ptychopetalum olacoides is a folk medicinal plant for health care in market, especially in Brazil. Fourteen known compounds were isolated from P. olacoides and their chemical structures were elucidated by extensive spectroscopic data, including 1D NMR, 2D NMR, UV, IR and HR-ESI-MS. The 14 known compounds were identified as N-trans-feruloyl-3, 5-dihydroxyindolin-2-one (1 ), magnoflorine (2 ), menisperine (3 ), 4-coumaroylserotonin (4 ), moschamine (5), luteolin (6 ), 4′-methoxyluteolin (7 ), 3-methoxyluteolin (8 ), 3, 7-dimethoxyluteolin (9 ), caffeic acid (10 ), ferulic acid (11 ), vanillic acid (12), syringic acid (13 ) and ginsenoside Re (14 ). To our knowledge, compounds (1 –6, 13 –14 ) were isolated from the plant for the first time. Additionally, quantitative analysis results indicated that calibration equations of compounds (1 –3, 6, 9, 11 –13 ) exhibited good linear regressions within the test ranges ( R 2 ≥ 0.9990) and magnoflorine and menisperine were the major constituents in the barks of P. olacoides . The contents of magnoflorine and menisperine accounted for 75.96% of all analytes. However, the content of phenolic components was smaller and the highest content was no more than 1.04 mg/g. Collectively, these results suggested that alkaloids are the dominant substances in P. olacoides, which can make a difference for the quality control and further use of P. olacoides. Abstract :